(untitled) (Research, Society and Development, 2021)
Studies involving cover crops in areas managed under no-tillage system are of great scientific relevance to seek the sustainability of agricultural crops. This study aimed to evaluate the impact of the use of cover crops on the structure of a clayey Oxisol under no-tillage system and its effect on corn yield. The treatments consisted of the use of six cover species: millet (Pennisetum glaucum), dwarf pigeon pea (Cajanus cajan), sunn hemp (Crotalaria juncea), pigeon pea (Cajanus cajan); crotalaria spectabilis (Crotalaria spectabilis Roth); black velvet bean (Stizolobium aterrimum) and the traditional no-tillage system (control). The experimental design used was completely randomized with 4 replications. The soil physical parameters evaluated were density, pore space and soil hydraulic conductivity. For this purpose, undisturbed soil samples were collected in the 0.00-0.10 m, 0.10-0.20 m and 0.20-0.30 m layers. After desiccation of the cover species, in full bloom, the corn crop was implemented. The corn grain yield was determined from 3 replicates of 13.5 m² of area each. Grain moisture was corrected to 13% to determine yield. The summer cover species that showed greater efficiency in soil restructuring were crotalaria spectabilis and black velvet bean. As for corn grain yield, there was no significant difference between treatments, evidencing the good structural conditions of the soil in the experimental area.